1986
DOI: 10.1128/iai.54.2.283-287.1986
|View full text |Cite
|
Sign up to set email alerts
|

Association with HeLa cells of Campylobacter jejuni and Campylobacter coli isolated from human feces

Abstract: We developed a rapid in vitro test for determining the association of Campylobacter jejuni and C. coli with HeLa cells. Association was expressed as a weighted mean of the number of bacteria associated with one cell in an association index (AI). The reproducibility of the AI was checked by repeating the test six times, using four strains chosen at random. Means and standard deviations of the means were 7.3 +/- 1.2, 6.8 +/- 0.9, 1.8 +/- 1.2, and 0.1 +/- 0.2. The experimental conditions for which the results are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
2

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(48 citation statements)
references
References 28 publications
2
44
0
2
Order By: Relevance
“…As in the case of other intestinal pathogens, the ability of C. jejuni to colonize the gastrointestinal tract by binding to epithelial or other cells has been proposed to be essential for disease production. Fauchere et al (1986) found that C. jejuni isolated from individuals with fever and diarrhoea exhibited greater binding to epithelial cells than strains isolated from individuals without diarrhoea or fever. Studies have been performed to identify and characterize potential Campylobacter adhesins that mediate the organism's attachment to host cells.…”
Section: Introductionmentioning
confidence: 88%
“…As in the case of other intestinal pathogens, the ability of C. jejuni to colonize the gastrointestinal tract by binding to epithelial or other cells has been proposed to be essential for disease production. Fauchere et al (1986) found that C. jejuni isolated from individuals with fever and diarrhoea exhibited greater binding to epithelial cells than strains isolated from individuals without diarrhoea or fever. Studies have been performed to identify and characterize potential Campylobacter adhesins that mediate the organism's attachment to host cells.…”
Section: Introductionmentioning
confidence: 88%
“…Adhesion to intestinal epithelial cells and their invasion are important for C. jejuni pathogenicity (Fauchere et al, 1986;Black et al, 1988;De Melo et al, 1989;Konkel et al, 1992), and CPS is thought to be essential for these processes (Bacon et al, 2001;Bachtiar et al, 2007). We therefore assessed our mutants for adhesion and invasion with Caco-2 intestinal epithelial cells.…”
Section: The Heptose Modification Pathway Is Important For Invasion Omentioning
confidence: 99%
“…Flagella-mediated motility also contributes to the virulence of C. jejuni (Biswas et al, 2007), as it facilitates colonization of the mucus layer covering the intestinal epithelium (Lee et al, 1986;Beery et al, 1988) and subsequent invasion of epithelial cells (Pei and Blaser, 1993;Jin et al, 2001;Konkel et al, 2005;Vijayakumar et al, 2006). Survival of C. jejuni within macrophages for several days is also a key virulence factor (Kiehlbauch et al, 1985;Day et al, 2000), and epithelial and macrophage cell damage resulting from invasion may be critical for the inflammatory response elicited by C. jejuni infection (Manninen et al, 1982;Newell and Pearson, 1984;Newell et al, 1985;Fauchere et al, 1986;Szymanski et al, 1995;Biswas et al, 2000). Further, the surface expression of lipooligosaccharide (LOS), which in many C. jejuni strains mimics human gangliosides, has been associated with autoimmune reactions implicated in the Guillain-Barre and Miller Fischer syndromes (Mishu and Blaser, 1993;Yuki et al, 1994;Salloway et al, 1996;Godschalk et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Following adherence, host-cell invasion and toxin production appear to contribute to C. jejuni pathogenesis and subsequent host cell tissue necrosis (Everest et al ., 1992;Konkel and Cieplak, 1992;Konkel et al ., 1993;Russell et al ., 1993;Wassenaar, 1997;Pickett and Whitehouse, 1999). Fauchère et al . (1986) found that C. jejuni isolates from individuals with fever and diarrhoea adhered to cultured cells at a greater efficiency than those isolates recovered from asymptomatic individuals.…”
Section: Introductionmentioning
confidence: 99%